Kaposi’s Sarcoma Associated with Gastrointestinal Bleeding : A Rare Complication of Long-Term Corticosteroid Therapy. - AZON KOUANOU, ANGÈLE; ZANNOU, DJIMON MARCEL; AGBODANDE, KOUESSI ANTHELME; ATTINSSOUNON, COSSI ANGELO; DOVONOU, ALBERT; PRUDENCIO, RDTK; BAGLO, TATIANA; HOUNGBE, FABIEN (My University, 2015)
Corticosteroid therapy has revolutionized the treatment of many diseases in medicine. The most concerned diseases are chronic inflammatory diseases. Its use may be either short-term or long-term, thus generating several side effects, some of which are conventional and known, but others are rare, such as Kaposi’s sarcoma. We report here a particular clinical observation. Observation: This is a patient of 37 years, who consults in Internal Medicine for the treatment of mucocutaneous lesions, papular nodular, hyper pigmented, budding and disseminated appeared after six months of corticosteroid therapy. This treatment was introduced for the treatment of acoustic neurinoma. The patient is not diabetic or alcoholic and has a negative HIV status. The diagnosis of Kaposi’s sarcoma was made by histology of biopsied skin lesions which concluded for a regular proliferation without atypia spindle cell or mitosis. The lesions persisted over a month despite discontinuation of corticosteroid therapy. Treatment with Bleomycin was necessary. The outcome was favorable under treatment with progressive and complete disappearance of lesions after 15 treatments. Conclusion: The classical side effects of long-term corticosteroid are known, but Kaposi sarcoma complicating long-term corticosteroid is rare in the literature. It is vital that any long-term corticosteroid should be the subject of careful and regular monitoring.
Keywords: Kaposi Sarcoma; Long-Term Corticosteroid; Rare Adverse Effects